Satyagraha opera in three acts - Glass, Philip 1937- (Orange Mountain Music, 2020)
The Metropolitan Opera Orchestra and Chorus under the direction of Dante Anzolini, perform Philip Glass's opera. Tenor Richard Croft, in the role of Gandhi, leads the stellar cast in a depiction of Gandhi's years in South Africa, during which he developed all his tools for social transformation through non-violence. Filmed during the 2011 production as part of the Met Opera's Live in HD Series
Bildformat: 16:9
Interpreten unter anderem: Richard Croft, Rachelle Durkin, Kim Josephson, Alfred Walker, Bradley Garvin, Richard Bernstein, Molly Fillmore, Maria Zifchak, Mary Phillips ; The Metropolitan Opera Orchestra And Chorus, Dante Anzolini, conductor
Enthält Bonusmaterial: Backstage at the Met: interviews with Philip Glass, Richard Croft, Donald Palumbo, Julian Crouch, Phil Eddolls and Rob Thirtle
Live in HD transmission on November 19, 2011
Keywords: Film; DVD-Video